Emotional problems arising from chronic disease in patients staying in the cardiology department - Wojarska, Izabela Kamila (Journal of Education, Health and Sport, 2017)
Introduction. In chronically ill people, subjective perceptions of well-being depend on distressing symptoms and level of satisfaction. An important issue in the fight against chronic disease is effective coping with the worsening circumstances of life. Aim. The goal is to know the emotional problems that can result from chronic illness, with special attention to social functioning, the emotional state of everyday life, the vitality and mental health of cardiac patients. Material and methods. The research group was randomly selected from the patients in the II Cardiology Clinic of the Świętokrzyskie Center of Cardiology. The study covered 72 people living in the city of Kielce and surrounding villages, aged between 45 and 85 years old. The control group consisted of 42 potentially healthy individuals randomly selected. The research method was a survey questionnaire, testing vitality, social functioning, impact of emotional state on daily life and mental health. Results and conclusions. The obtained results illustrated the emotional state, psychological well-being and social relations of patients. Chronic illnesses, in this case cardiac diseases, have a negative impact on the mental functioning of a person, and thus generate a lower quality of life than a healthy population. Women are characterized by a higher level of social functioning compared to men, while men are more likely than women to be vitally active and generally mentally healthy. Patients with ischemic heart disease, surgical intervention and those suffering from cardiac dysrhythmias do not differ from each other in terms of measured domains, this may mean that patients with these groups have the same emotional problems.